2022
DOI: 10.3389/fnut.2021.802352
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of Gut Microbiota and Plasma Metabolites Reveals the Effect of Red-Fleshed Apple Anthocyanin Extract on Dysfunction of Mice Reproductive System Induced by Busulfan

Abstract: Busulfan is currently an indispensable anti-cancer drug, but the side effects on male reproductive system are so serious. Meanwhile, red-fleshed apples are natural products with high anthocyanin content. In this research, we analyzed the effect of red-fleshed apple anthocyanin extract (RAAE) on busulfan-treated mice. Compared with the busulfan group, main plasma biochemical indicators were significantly improved after RAAE treatment. Compared with BA0 (busulfan without RAAE) group, total antioxidant capacity(T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Many recent studies of building sterile animal models have utilized busulfan as a treatment [20]. The preparation of RAFEs has been previously described in our publication [28].…”
Section: Treatment Of Mousementioning
confidence: 99%
See 2 more Smart Citations
“…Many recent studies of building sterile animal models have utilized busulfan as a treatment [20]. The preparation of RAFEs has been previously described in our publication [28].…”
Section: Treatment Of Mousementioning
confidence: 99%
“…The samples were then embedded in paraffin blocks and cut into 5 µm sections using standard histological ob-servation procedures. The prepared paraffin sections were stained with H&E following previous procedures [20]. The testicular paraffin sections were also used for immunohistochemistry, but antigen retrieval was required after removing the organic solution.…”
Section: Hande and Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Xu et al found that red-fleshed apple anthocyanin extract (RAAE) alleviates busulfan-induced dysfunction of the male reproductive system in mice ( 28 ) by enhancing sperm motility, increasing the number of mice, and restoring spermatogenesis in male mice. Wang et al further analyzed the mechanism by which RAAE alleviates busulfan-induced reproductive system dysfunction in mice ( 29 ), and found that the total antioxidant capacity (T-AOC), SOD activity, and glutathione catalase activity were significantly increased in the RAAE treatment group, indicating that RAAE can reduce the oxidative injury of busulfan in mice by reducing the content of reactive oxygen species and restoring the reproductive system function of mice. Previous research has also shown that red-fleshed apple flavonoid extract (RAFE) has antioxidant and cell viability maintenance capabilities; however, little research has explored the effects of red-fleshed apple flavonoids on CCl 4 -induced liver injury in mice.…”
Section: Introductionmentioning
confidence: 99%
“…We had previously compared four varieties of red-fleshed apples and found that variety ‘XJ4’ had the highest total phenol and anthocyanin contents with a strong ability to scavenge free radicals ( 27 ). At the same time, we previously treated mice with busulfan-induced reproductive injury with ‘XJ4’ anthocyanin extract, and the combined analysis of microbiota and plasma metabolites showed that ‘XJ4’ anthocyanin extract could reduce busulfan-induced reproductive injury ( 29 ). So we selected ‘XJ4’ as the experimental material, and the control was the white-fleshed apple ‘Fuji’.…”
Section: Introductionmentioning
confidence: 99%